2010
DOI: 10.4314/just.v29i3.50028
|View full text |Cite
|
Sign up to set email alerts
|

Pollen grain morphology of three species and a variety of Ocimum linn.(Lamiaceae) in Southwestern Nigeria

Abstract: Pollen grains from fresh anthers of three species and a variety of Ocimum occurring in Southwestern Nigeria were collected and acetolysed. This was in an attempt to use the pollen characteristics to delimit, classify and trace probable evolutionary relationships among the taxa. The structural morphology of the pollen grains carried out with a light microscope is reported. Characters measured on the pollen grains were pollen diameter, pollen wall thickness, depth of colpi, distance between colpi and pore diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Harley et al (1992) found in their studies that most of Ocimum species pollens are with bireticulate-perforate tectum sculpture and suggested a re-evaluation in their classification. As well as Arogundade and Adedeji (2009) in their study of Ocimum L. species concentrated on pollen colpi reporting different types of pollens acolpate to octacolpate pollens which reveal that there are significant differences among the species. Moreover, Dinç et al (2009) reported in their study on Lallemantia species growing in Turkey, the exine sculpture of pollen had taxonomic value.…”
Section: Introductionmentioning
confidence: 96%
“…Harley et al (1992) found in their studies that most of Ocimum species pollens are with bireticulate-perforate tectum sculpture and suggested a re-evaluation in their classification. As well as Arogundade and Adedeji (2009) in their study of Ocimum L. species concentrated on pollen colpi reporting different types of pollens acolpate to octacolpate pollens which reveal that there are significant differences among the species. Moreover, Dinç et al (2009) reported in their study on Lallemantia species growing in Turkey, the exine sculpture of pollen had taxonomic value.…”
Section: Introductionmentioning
confidence: 96%
“…Pollen shapes have been found useful in the delimitation of groups of plants (Moore and Web, 1978;Arogundade and Adedeji, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Palynological evidences have proven useful at all taxonomic levels because the structure of the pollen wall which is usually being employed in the study is not affected by environmental factors Nnamani and Onu (2014). Palynological characters have therefore been variously employed in the taxonomy of species of plants, forensic sciences, crime site detection, archaeology, paleoecology, delimitation of closely related or sympatric species, valuable in phylogenetic inferences (Nyananyo, 1992;Akinwusi and Illoh, 1996;Edeoga et al, 1998;Adedeji, 2005;Arogundade and Adedeji, 2009;Simpson, 2010, Arogundade andLawal, 2018). According to Acharya et al (2011), there are still a lot of taxonomic work to be done at the genera and specific levels of the subfamily Caesalpinioideae.…”
Section: Introductionmentioning
confidence: 99%
“…), Hierocymum Benth and Gymnocymum Benth. Pollen grains of three species and a variety of Ocimum occurring in South-western Nigeria by light microscopy (LM) have been reported by Arogundade and Adedeji (2009). Morphological characteristics of family Lamiaceae of seeds of Al-Taif in Saudi Arabia are focused by Hassan and Altobatti (2015) and formerly by El-Gazzar and Watson (1970).…”
Section: Introductionmentioning
confidence: 99%